Anisotropic plasmonic Pd-tipped Au nanorods for near-infrared light-activated photoacoustic imaging guided photothermal–photodynamic cancer therapy. Issue 12 (7th March 2022) - Yang, Chen; Jiang, Wenli; Yu, Yongqi; Zhang, Hui; Cai, Chenxin; Shen, Qingming
Abstract : Anisotropic plasmonic Pd-tipped Au nanorods were successfully fabricated for photoacoustic imaging-guided photothermal and photodynamic therapy under near-infrared laser irradiation. Abstract : The integration of photothermal therapy (PTT) and photodynamic therapy (PDT) has become a promising cancer treatment method. Herein, anisotropic metal hetero-nanostructure Pd-tipped Au nanorods (PTA NRs) were fabricated, which exhibit plasmon-enhanced photothermal performance under near-infrared laser irradiation. Due to their anisotropic nanostructure, PTA NRs promote the generation of energetic hot electrons and prolong the separation time of electrons and holes. The hot electrons could generate heat energy through the electron–phonon relaxation process and produce reactive oxygen species through energy and electron transformation processes. Because of their high NIR absorption cross-section, as well as good photostability, PTA NRs can be used for NIR-activated photoacoustic imaging-guided PTT-PDT combination cancer therapy. Experiments in tumor-bearing mice proved that PTA NRs exhibit excellent anti-tumor effects, with little side effects on normal organs, making them promising for NIR cancer phototherapy.